Phylogenetic, molecular, and microscopic investigation of Linguatula serrata infection in stray and road-killed dogs in Northwest Iran - Hajipour, Nasser; Ghorani, Mohammadreza; Ketzis, Jennifer (BMC veterinary research, 2025)
Background Linguatula serrata is a cosmopolitan zoonotic parasite. Canids serve as definitive hosts, while herbivores acts as intermediate hosts. Adult L. serrata are found in the nasal and respiratory passages, whereas the immature stages are located in the mesenteric lymph nodes, liver, spleen, lungs, and, occasionally in other organs. Humans can serve as intermediate hosts, with visceral infections, or as definitive hosts with nasopharyngeal infections. This study aimed to investigate the infection rate of stray and road-killed dogs with L. serrata and to explore its phylogeny. Material and methods A total of 150 stray dogs and 100 road-killed dogs were examined for L. serrata eggs in feces and nasal secretions using microscopy and molecular tests, and for adult L. serrata through necropsy. Results The results showed that 174 of 250 (69.6%) studied dogs were positive for L. serrata by at least one of the examination methods. The prevalence in road-killed and stray dogs was determined to be 72% and 68%, respectively. The L. serrata infection rate based on fecal microscopy in the road-killed and stray dogs was 29% and 46.7%, respectively, and by fecal PCR was 59% and 48.7%, respectively. The rate of infection with L. serrata based on nasal secretions in road-killed and stray dogs was 14% and 26%, respectively, using microscopy, and 44% and 43.3%, respectively, using PCR. In the road-killed dogs, based on necropsy, 46% were positive. The results of this study show that PCR is more effective than microscopy for detecting L. serrata infections in dogs. PCR amplicon of the expected size for Linguatula of approximately 595 bp for 18S rRNA were generated from the L. serrata isolates using described specific primers. Conclusion It can be concluded that the rate of infection in dogs and possibly other carnivores, herbivores, and man, is high in this locality; hence, strict control measures should be conducted to overcome the risk of infection with this zoonotic disease.